What Caused the Global Financial Crisis : Evidenceon the Drivers of Financial Imbalances 1999; 2007 - Merrouche, Ouarda (IMF Working Papers; Working Paper ;, 2010)
This paper investigates empirically the drivers of financial imbalances ahead of the global financial crisis. Three factors may have contributed to the build-up of financial imbalances: (i) rising global imbalances (capital flows), (ii) monetary policy that might have been too loose, (iii) inadequate supervision and regulation. Panel data regressions are performed for OECD countries from 1999 to 2007, so as to shed light on the relative importance of these factors, as well as the extent to which these factors might have interacted in fuelling the build-up. We find that the build-up of financial imbalances was driven by capital inflows and an associated compression of the spread between long and short rates. The effect of capital inflows on the build-up is amplified where the supervisory and regulatory environment was relatively weak. We find that, by contrast, differences in monetary policy cannot account for differences across countries in the build-up of financial imbalances ahead of the crisis.